Strategy to Improve the Performance of Port Workers Yos Sudarso Tual City through the Work Environment and Job Satisfaction - Ferdy Leuhery; Yesai Masbaitubun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Objectives – This study aims to test the effect of the work environment on the performance of the transport workers and test the effect of job satisfaction on the performance of transportation workers employees. Design/methodology/approach – This study uses quantitative methods. Sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical with the aim of testing predetermined hypotheses. Practical implications – This study recommends that expected to add references and discourses to develop knowledge about human resource management, especially those related to the work environment and job satisfaction and their impact on employee performance. Originality/value – This study provides to job satisfaction with indicators Satisfaction with salary, Satisfaction with working conditions, Satisfaction with coworkers, Satisfaction with supervisors, Satisfaction with the work itself to detail, results-oriented, human-oriented, team-oriented, aggressiveness and stability affect the performance of the Kairatu Public Health Center, then the hypothesis is accepted.